Odpowiedzi

Najlepsza Odpowiedź!
2010-04-09T19:11:59+02:00
X+y= (1+4√3)+(4-2√3)= 5+2√3

x-y= (1+4√3)-(4-2√3)= 1+4√3-4+2√3= -3+6√3

xy= (1+4√3)(4-2√3)= 4-2√3+16√3-24= 14√3-20

x/y= 1+4√3/4-2√3= (1+4√3)(4+2√3)/(4-2√3)(4+2√3)= 4+2√3+16√3+24/16-12= 16√3+28/4= 4√3+12

x²= (1+4√3)²= 1+8√3+48= 8√3+49

2x-3y= 2(1+4√3)-3(4-2√3)= 2+8√3-(12+6√3)= 2+8√3-12-6√3= -10+2√3
1 5 1
  • Użytkownik Zadane
2010-04-09T19:12:48+02:00
X+y
1+4/3+4-2/3=1+1,3+4-0,7=2,3+3,3=5,6
x-y
1+ 4√3-4-2√3=1+1,3-4-0,7=2,3-3,3=1
xy
x*y=1+ 4√3*4-2√3=1+1,3*4-0,7=1+5,2-0,7=6,2-0,7=5,5
x/y
1+ 4√3/4-2√3=1+1,3/4-0,7=1+0,325-0,7=1,325-0,7=0,625

x²=x*x=1+4/3*1+4/3=1+1,3*1+1,3=1+1,3+1,3=3,6
2x-3y
2*1+4/3-3*4-2/3=2+1,3-12-0,7=3,3-12-0,7=3,3-11,3=7

* razy
/ podzielić
+ dodać
* odjąć



MyŚlę ę dobrze ;**
1 5 1